Assessment of topical bakuchiol and retinol for facial photoageing. (4th February 2019) - Dhaliwal, S.; Rybak, I.; Ellis, S.R.; Notay, M.; Trivedi, M.; Burney, W.; Vaughn, A.R.; Nguyen, M.; Reiter, P.; Bosanac, S.; Yan, H.; Foolad, N.; et al.
Summary: Bakuchiol is found mainly in the seeds of the Indian plant Psoralea corylifolia (babchi) and has recently been shown to have a number of antioxidant and anti‐inflammatory properties. The goal of this study, by researchers from universities in California, Michigan, Florida and Pennsylvania in the US, was to compare the efficacy and side effects of bakuchiol with the commonly‐used anti‐ageing ingredient retinol. 44 volunteers were asked to apply either bakuchiol 0.5% cream twice daily, or retinol 0.5% cream daily, to facial skin for 12 weeks. Retinol 0.5% has previously been shown to be effective at preventing and addressing signs of skin ageing but can have side effects including stinging, scaling and redness. A facial photograph and analytical system was used to take and analyse high‐resolution photographs of patients at 0, 4, 8 and 12 weeks of the study. Patients also answered questions about side‐effects. During study visits, a dermatologist graded pigmentation (skin colouring) and redness. To avoid bias, this dermatologist was not made aware of which treatment each participant was using. The study found that bakuchiol and retinol both significantly decreased wrinkle surface area and hyperpigmentation, with no statistical difference between the two compounds. However, the retinol users reported more skin scaling and stinging. The results were most marked after the full 12 weeks, with a 20 percent reduction in wrinkle severity. 59 percent of the participants in the bakuchiol group showed improvement in their hyperpigmentation at week 12, compared to 44 percent of those in the retinol group. The improvements related both to the intensity of the colour and to the size of the area affected. The findings of this study are promising for bakuchiol as an effective anti‐ageing treatment with minimal side effects, however this would need to be confirmed in larger studies. Abstract : Linked Article: Dhaliwal et al. Br J Dermatol 2019; 180 :289–296